Study to propose a post- impact assessment framework for science and technology policy - Anh, Pham Quynh; Ha, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The system of science and technology (S&T) legal documents in Vietnam is increasingly completed. Together with the issuance of specific guidelines for the implementation of the Law on S&T, the State has promulgated a number of specialized laws to amend or supplement one or various issues of S&T activities. This provides a legal framework for S&T operation in Vietnam. In fact, a number of S&T policies has been put into effect, but the question of whether their objectives have been achieved, what are their impacts on organizations/individuals working in the field of S&T, as well as on socio-economic, S&T and other sectors’ development, are still pending with proper answer due to no proper attention has been so far paid to S&T policy impact assessment in Vietnam. In the scope of this article, the author introduced the concept and role of S&T policy impact assessment in S&T management, highlighted its advantages and disadvantages in realizing this exercise in Vietnam, and based on that, proposed a framework for post assessment of the impact of S&T policies. Code: 16051001<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">